Samples in Educational Research. A Study of Relevance and Sufficiency in Graduate Theses - Esquivel-Grados, José Theódulo; Venegas-Mejía, Clotilde Paula; Esquivel- Grados, Migdonio Nicolás; Gonzales-Benites, Manuel Tomás (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Analyzing the sufficiency and relevance of the samples in master's theses is the objective of the article, the result of a descriptive study with a documentary approach, whose population were master's theses in accreditation of the educational quality of four Universities of Lima, 2020-2022. Observation was used to collect data, finding as results that in the theses carried out mostly with a quantitative approach it is not frequent to observe adequate or representative samples, since they do not offer a logical or methodological justification on how the sample size and the use were determined. of sampling techniques; while in the few qualitative investigations, no arguments are presented to ensure the relevance and sufficiency of the sample, which in both cases affects the quality of the information collected and the convenient volume to obtain reliable results.